Integrating crisis learning into futures literacy – exploring the “new normal” and imagining post-pandemic futures - Karjalainen Joni; Mwagiru Njeri; Salminen Hazel; Heinonen Sirkka (Emerald, 2022)
Purpose
Crises are major events or periods faced by individuals, groups and society. This paper aims to explore the value of facilitating (un)learning in and from crises. Educators have a key role in building futures literacy (FL) for dealing with uncertainties, understanding emergence and responding to rapid, complex change. Integrating crisis learning as part of FL is important for enhanced anticipatory and crisis responses.
Design/methodology/approach
Adapting from causal layered analysis (CLA) methodology, experimental virtual futures workshops were designed and hosted during the coronavirus pandemic. Participants discussed COVID-19 crisis responses and imagined the “new normal”. Sessions explored mindsets applied to make sense and derive meaning from the crisis, myriad ways of adapting to uncertainty, as well as lenses used to imagine post-crisis futures.
Findings
In the exploratory and participatory CLA exercises, participants shared on the COVID-19 pandemic and imagined post-crisis futures. Related hopes and fears concerned self, collectives and nature. Overall, despite the dramatic nature of crises, opportunities exist for learning and transformation. Educators play a central role in heightening awareness about the dynamics and nature of crises, and integrating crisis learning into FL, as important and transformative capabilities.
Research limitations/implications
In exploratory dialogues, the “new normal” was applied as a frame for uncertainty. The workshops were hosted during the COVID-19 pandemic as a specific type of crisis. The workshop design is intended to be replicable in various crisis contexts and for iterative rounds with diverse groups. Therefore, futures images exemplify context-specific crisis-time sentiments. The findings presented here do not aim to be generalizable. They are liable to change across different crises, as a crisis evolves and across diverse stakeholders.
Practical implications
Dramatic change and crisis events offer potential moments for development, advancement and transformation. Educators have an important role in facilitating (un)learning in and from crises, elevating FL and expanding futures consciousness. The CLA methodology can assist educators to engage with multiple facets, layers and dimensions of crises. By considering crises intently, educators can help in anticipating emergence, imagining and preparing for diverse alternatives.
Social implications
The contemporary world is volatile, complex and ambiguous volatile, uncertain, complex and ambiguous (VUCA), as revealed by multiple crises. Crises can spotlight new possibilities and horizons and may be possible turning points. The COVID-19 is an example of a crisis disruption, which provoked thinking and contributed to action about novel prospects. To realise transformative change however, it is important to integrate crisis learning as part of FL, and here educators are an important influence.
Originality/value
Integrating crisis learning into FL is proposed to improve responses to the rapid pace of change and uncertainty as well as to boost crisis preparedness. As part of this, there is value in applying and developing techniques such as CLA that help explore and question assumptions, to understand diverse, possible and transformed futures. This way, we can explore, imagine and expand new horizons.